Phytoconstituents, In Vitro Anti-Infective Activity of Buddleja indica Lam., and In Silico Evaluation of its SARS-CoV-2 Inhibitory Potential - Youssef, Fadia S.; Altyar, Ahmed E.; Omar, Abdelsattar M.; Ashour, Mohamed L. (Frontiers in Pharmacology, 2021)
Phytochemical investigation of Buddleja indica Lam. leaves methanol extract (BIT) resulted in the isolation of six known compounds for the first time from the plant namely; p-hydroxy benzoic acid (1), caffeic acid (2), quercetin 3-O-β-D glucoside-7-O-α-L-rhamnoside (3), kaempferol 3-O-β-D glucoside-7-O-α-L-rhamnoside (4), quercetin 7-O- β-D glucoside (5) and kaempferol (6). BIT extract showed a potent antibacterial activity with MIC values ranging between 0.48 – 1.95 µg/mL with Bacillus subtilis was the most susceptible to BIT effect. It showed a notable anti-mycobacterial and anti- Helicobacter pylori activity with MIC value of 100 and 80 µg/mL, respectively. Vesicular stomatitis virus (VSV) was more sensitive to the antiviral activity of BIT comparable to herpes simplex virus type-1 (HSV-1) showing 48.38 and 41.85% inhibition of the viral replication at a dose of 50 μg/mL for VSV and HSV-1, respectively. In silico molecular docking of the isolated compounds revealed that caffeic acid (2) showed the highest fitting within the active sites of DNA-gyrase, topoisomerase IV as well as SARS-CoV-2 MPro . Quercetin 7-O- β-D glucoside (5) revealed the best fitting in dihydrofolate reductase active site with ∆ G value equals -36.53 Kcal/mol. Kaempferol (6) exhibited the highest fitting towards β-lactamase, SARS-CoV-2PLpro, SARS-CoV-2 3CLpro active sites. Thus B. indica Lam. can be considered as a future source of cheap, substantially safe and credible antibacterial, antifungal and antiviral candidate of natural origin that could effectively participate in solving the problem of COVID-19 pandemic. These findings provide a scientific consolidation for the ethno-medicinal uses of Buddleja indica Lam. as a topical antiseptic.